Feasibility analysis for reduction of carbon footprint in a wastewater treatment plant. (20th October 2020) - Borzooei, Sina; Campo, Giuseppe; Cerutti, Alberto; Meucci, Lorenza; Panepinto, Deborah; Ravina, Marco; Riggio, Vincenzo; Ruffino, Barbara; Scibilia, Gerardo; Zanetti, Mariachiara
Abstract: This study presents an integrated feasibility analysis approach to reduce the carbon footprint in the largest Italian wastewater treatment plant (WWTP). Firstly, a model-based feasibility analysis was carried out to assess the applicability of upgrading scenarios, for an ongoing anaerobic sludge digestion process. Application of dynamic sludge thickener, as well as hybrid thermo-alkali pre-treatment of waste activated sludge, were assessed to enhance the biogas production in the WWTP. Further, an implementation of the selective membranes was proposed and studied to upgrade the produced biogas in sludge treatment units to biomethane with an average efficiency of 98.6%. Model-based sludge pre-treatment and biogas upgrading strategies were developed and evaluated in terms of mass, energy, and greenhouse gas emission balance. The obtained results prove that practicing the proposed upgrading scenario can lead to an 18% improvement in biogas production and a significant reduction of thermal energy auto-consumption and total greenhouse gas emissions. In the second phase, the laboratory-based feasibility analysis was performed about the integration of microalgae technology into the current process of the WWTP. A planar photobioreactor was built to estimate the volumetric mass transfer coefficient (KL a) and CO2 consumption of the reactor. By the use of 44 and 76 μmol/m 2 /s light intensities, the results show 80% and 70% reductions in total CO2, respectively. The tested configuration guaranteed 11.763 and 27.943 mg/l/h CO2 consumptions, as well as 0.5775 h −1 and 17.7 h −1 KL a values. Overall, the results prove that applications of the technologies proposed in this study can significantly reduce the carbon footprint of the WWTP. Graphical abstract: Image 1 Highlights: Model-based sludge pre-treatment and biogas upgrading scenarios are evaluated in a WWTP. Various upgrading scenarios are studied and compared in terms of mass, energy, and GHG balance. Application of dynamic sludge thickener, hybrid thermo-alkali sludge pre-treatment and biomethane production are proposed. Use of an experimental microalgae technology is considered for CO2 fixation. Experimental setup is proposed to evaluate the KLa of CO2 in the microalgae system.